Irrigation Projects and the Egyptian Bedouin - El-Khodari, Nabil M. (Water Nepal, 2003)
The Sainai desert is habitation of indigenous Bedouin population. With a loan from the World Bank the Egyptian Government planned the northern Sinai Agricultural Development Project (NSADP). This project however faced a major problem in integrating the Bedouin in the project. An environmental impact assessment of the project was done ignored by the government. Using this report, this paper discusses the social impacts of the project on the Bedouins of North Sinai. Project planners failed to look at some of shortcomings which are discussed. The root cause of the anticipated social and political unrests is enumerated. Lastly, some alternatives and preventive measures are recommended. Water Nepal Vol.9-10, No.1-2, 2003, pp.409-419